The Dynamics of Bachelor of Social Studies Education Study Program FKIP Universitas Lambung Mangkurat Period 2014–2023 - Dhimas Pratama Nindya Putra Sari; Ersis Warmansyah Abbas; Eva Alviawati; Syaharuddin Syaharuddin; M. Ridha Ilhami; Helmi Akmal; Rusli Rusli (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
This study aims to describe and analyze the institutional development of the Social Studies Education Study Program, Faculty of Teacher Training and Education, Lambung Mangkurat University (ULM), during the period 2014–2023 and its relation to achieving the Top Department SINTA recognition in 2022. The research employed a qualitative approach using the historical research method through the stages of heuristics, source criticism, interpretation, historiography, and chronological analysis of institutional documents, publication reports, study program archives, and in-depth interviews with academic leaders and lecturers. The results indicate strengthened organizational structure, an increased number of home-based lecturers, and a significant rise in scientific publication productivity through the establishment of three internal journals: The Innovation of Social Studies Journal (ISSJ), Kalimantan Social Studies Journal (KSSJ), and Journal of Social Development (J-SOD). The integration of institutional policy with publication strategies fostered a productive academic culture, while transformational leadership contributed to enhancing lecturers' motivation to write. This study recommends continuous scientific writing training and the implementation of a performance-based incentive system as strategic efforts to sustain and improve the study program's achievements.